Preparing for AI's Transformational Potential: Rethinking Teacher Education in South Africa - Tarisayi, Kudzayi Savious (Angstrom Centre of Education, 2024)
As artificial intelligence (AI) increasingly reshapes education, teacher training must evolve to effect positive change. This paper analyses strategies for rethinking teacher education in South Africa to integrate AI competencies. With over 420,000 teachers facing challenges like under preparation and classroom diversity, AI's personalized capabilities could assist instruction. However, actualizing this potential requires teacher training reforms aligned to pedagogical goals. Grounded in competency education and social cognitive theories, this paper recommends four priorities: hands-on AI workshops modelling differentiation, scaffolded online learning, peer sharing networks, and expert coaching via digital badging. Analysis suggests these approaches develop AI integration competencies through situated learning while upholding humanistic aims. Recommendations emphasize competency-based progression focused on pedagogies like differentiation in diverse contexts. Online modules provide fundamental knowledge before experiential application. Peer communities enable collaborative mastery through observation and exchange. Expert mentoring guides contextualized skill development, verified through credentials. This competency focus promotes agency and recognizes teacher knowledge. Rethinking teacher education will be crucial as South Africa transforms education. Adopting strategies like competency mentoring and sharing networks can empower teachers to direct change. Sustained, aligned policies supporting teacher professionalization will complement training. With teachers guiding integration, AI can enrich learning experiences. This paper offers principles and evidence-based strategies for human-centred teacher education reform.